Study of methanogen communities associated with different rumen protozoal populations. Issue 3 (29th September 2014) - Belanche, Alejandro; de la Fuente, Gabriel; Newbold, Charles J.
Abstract Protozoa‐associated methanogens (PAM) are considered one of the most active communities in the rumen methanogenesis. This experiment investigated whether methanogens are sequestrated within rumen protozoa, and structural differences between rumen free‐living methanogens and PAM. Rumen protozoa were harvested from totally faunated sheep, and six protozoal fractions (plus free‐living microorganisms) were generated by sequential filtration. Holotrich‐monofaunated sheep were also used to investigate the holotrich‐associated methanogens. Protozoal size determined the number of PAM as big protozoa had 1.7–3.3 times more methanogen DNA than smaller protozoa, but also more endosymbiotic bacteria (2.2‐ to 3.5‐fold times). Thus, similar abundance of methanogens with respect to total bacteria were observed across all protozoal fractions and free‐living microorganisms, suggesting that methanogens are not accumulated within rumen protozoa in a greater proportion to that observed in the rumen as a whole. All rumen methanogen communities had similar diversity (22.2 ± 3.4 TRFs). Free‐living methanogens composed a conserved community (67% similarity within treatment) in the rumen with similar diversity but different structures than PAM (P < 0.05). On the contrary, PAM constituted a more variable community (48% similarity), which differed between holotrich and total protozoa (P < 0.001). Thus, PAM constitutes a community, which requires further investigation as part of methane mitigation strategies.